EXPERIENCING POETRY: UNLEARNING AND RELEARNING LITERATURE TO DEVELOP READING INTERESTS IN LITERARY WORKS - Musthafa, Bachrudin (UPI Press, 2013)
Building on results of a classroom-based survey on studentsâ€™ literacy habits, this article reportson how an exploratory study on experiencing poetry can change EFL studentsâ€™ â€œways withliterature.â€ First problems from past experiences with literature are discussed and theoreticalinsights proposed which will bring to fore the need for a change in pedagogical orientations.Next the idea of â€œexperiencing poetryâ€ is flashed out by addressing the knotty problemsliterature teaching has been faced with. Step-by-step instructional procedures are discussedtogether with their corresponding pedagogical considerations. Some guiding pedagogicalprinciples are then proposed and discussed to complete the workshop. From this exploratorystudy, it is evident that students learned from one another in the context of sharing of literaryexperiences and from observing how the literature instructor as a more knowledgeable memberof the culture demonstrated the way he experienced the poem he was reading. More specifically,from experiencing poetry and sharing about what they like from what they experience andenjoy, students learn to reflect critically on what they get from reading.Keywords: experiencing poetry; EFL literature-learning; literature for empowerment